Spaces of absolutely summing polynomials - Barbosa, J.A.; Botelho, G.; Diniz, D.; Pellegrino, D. (MATHEMATICA SCANDINAVICA, 2007)
This paper has a twofold purpose: to prove a much more general Dvoretzky-Rogers type theorem for absolutely summing polynomials and to introduce a more convenient norm on the space of everywhere summing polynomials.